2006
DOI: 10.1016/s0022-5347(05)00708-1
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Factors as Predictors of Clinical Progression of Benign Prostatic Hyperplasia in Men Treated With Placebo

Abstract: Among men in the placebo arm, baseline TPV, PSA, Qmax, PVR and age were important predictors of the risk of clinical progression of BPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
134
0
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(155 citation statements)
references
References 17 publications
13
134
0
8
Order By: Relevance
“…Baseline total prostate volume, PSA, Qmax, post void residue and age were important predictors of the risk of clinical progression of BPH (Crawford et al, 2006). According to our results, NLR, with a cut-off value of 1.99, can be used in conjunction with other parameters in predicting the progression of BPH.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Baseline total prostate volume, PSA, Qmax, post void residue and age were important predictors of the risk of clinical progression of BPH (Crawford et al, 2006). According to our results, NLR, with a cut-off value of 1.99, can be used in conjunction with other parameters in predicting the progression of BPH.…”
Section: Discussionmentioning
confidence: 51%
“…The low risk group was characterized by a PSA <1.6ng/mL, prostate volume <31mL, age <62 years, IPPS <20 points, Qmax ≥10.6mL/second; the high risk group included individuals with a PSA ≥1.6 ng/ mL, prostate volume ≥31mL, age ≥62 years, IPPS ≥20 points, and Qmax <10.6mL/second (Crawford et al, 2006;SpringerBasicRoehrborn et al, 2014). NLR was compared between the low-and high-risk groups.…”
Section: Study Populationmentioning
confidence: 99%
“…In medical therapy of prostate symptoms, subjects in the placebo arm with a baseline PVR greater than 39 ml had statistically significant higher progression rates, including symptom score progression, rates of AUR and surgical therapy. 72 In patients on medical therapy, however, baseline PVR did not predict outcomes. 79 Overall, in clinical trials, the importance of PVR as a predictor of BPH progression may be underestimated, as most trials exclude patients with large baseline PVRs.…”
Section: Post-void Residual Volumementioning
confidence: 99%
“…71 In the placebo arm of the medical therapy of prostate symptoms, men with a maximum flow rate o10.6 ml s À1 at baseline had a greater risk of overall progression, symptomatic progression and incidence of surgical intervention. 72 Maximum flow rates have been seen to exhibit an age-related component. The decrease in urinary flow rates with age is approximately linear.…”
Section: Maximum Flow Ratesmentioning
confidence: 99%
“…1,2 Crawford et al reported that a PV of ≥31 mL was one of the important predictors for the risk of clinical progression of BPH, including progression of the International Prostate Symptoms Score, the occurrence of urinary retention and development to an invasive procedure. 3 For the BPH patient who has an enlarged prostate with a size >30 mL, previous large clinical trials such as the MTOPS trial and CombAT trial showed the effectiveness of combination therapy with a 5-a-reductase inhibitor and an ablocker. 4,5 Although the risks and treatment for the enlarged prostate have been reported, there have not been many reports on evaluation of the PV.…”
Section: Introductionmentioning
confidence: 99%